The Effect Of Blended Learning Of Student Teams Achievement Division (Stad) And Jigsaw Towards Higher-Order Thinking Skills - Kurniawan, Sandi; Sutadji, Eddy; Sudjono, Imam (Universitas Negeri Padang, 2020)
Higher order thinking skills (HOTS) are abilities that should be possessed by all vocational high School (VHS) students, because VHS graduates are required to have good soft skills and hard skills. The reality that occurs the ability of HOTS possessed by students is still very low, it is proven based on the exposure of several researchers strengthened by conducting observations and observations in VHS. Therefore the research aims to determine student learning activities when taught using blended learning Student Teams Achievement Division (STAD) and jigsaw, using direct learning models, and their effects on HOTS. This research is a quantitative study with a quasi experimental nonequivalent control group design method with research subjects of 50 students using simple random sampling. Data collection techniques using the test instrument in the form of multiple choice and description and non-test instruments in the form of observation sheets. Research data were analyzed by independent sample t-test. The results showed that the use of STAD and jigsaw blended learning in learning made students more active and enthusiastic in participating in learning activities, direct learning models made students less active and lacked enthusiasm in the learning process, and STAD and jigsaw blended learning significantly affected compared to learning models directly to HOTS.